Beyond “best practices”: Centering equity in teacher preparation evaluation - Cochran-Smith, Marilyn; Reagan, Emilie (Education Policy Analysis Archives, 2022)
Over the last decade, there have been multiple recommendations for evaluating, assessing, or holding teacher preparation accountable. This article analyzes recent policy proposals regarding “best practices for evaluating teacher preparation programs” by critiquing 19 major reports explicitly focused on evaluation. The analysis revealed that the reports’ primary goal was identifying preferred evaluation metrics using rigorous criteria for accuracy and utility. The majority of reports did not position equity as a central goal of evaluation and actually said little about equity explicitly, although some assumed equity was a by-product of rigorous evaluation systems. Building on previous efforts to focus on equity in teacher education, the article advocates an equity-centered approach to teacher preparation evaluation that acknowledges long-standing inequities in educational opportunity and attainment in the United States. Rejecting the idea of “best practices,” which are by definition decontextualized and inattentive to local contexts, the article offers 11 guiding principles for researchers, policymakers, and practitioners, to make strong equity the center of evaluation. These recommendations include: making equity an explicit goal during the entire process of evaluation and working at a systems/structural level; utilizing assessment models and tools that focus on equity; including all stakeholders, especially those from the minoritized communities served by programs, in decisions about evaluation criteria; and, supporting internal professional accountability.